Agricultural biogas plants – A systematic analysis of strengths, weaknesses, opportunities and threats. (January 2015) - Brudermann, Thomas; Mitterhuber, Corinna; Posch, Alfred
Abstract: In this paper, we discuss the prospects of agricultural biogas plants. We conducted an integrated SWOT–AHP analysis for such plants in Austria in order to identify strengths, weaknesses, opportunities and threats (SWOT factors), and to weight the factors identified based on expert judgments, calculated according to the Analytic Hierarchy Process (AHP) method. The results show that financial aspects are dominant in three of the four SWOT categories. Technological aspects and issues regarding utilization seem to play a relatively minor role. Factors that are not directly under the control of plant operators are currently perceived as crucial for the success of agricultural biogas plants. We conclude that such plants will only succeed in contributing to sustainable energy supply goals when economic and political conditions are favorable over the long term. Highlights: Integrated SWOT–AHP analysis for agricultural biogas plants in Austria. Quantification of weighting factors based on expert judgments. Financial aspects dominate over technological and environmental aspects. Sophisticated and flexible subsidy schemes are crucial for the further diffusion of the technology.